1992
DOI: 10.1088/0960-1317/2/2/004
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic microstructures for the measurement of intrinsic strain in thin films

Abstract: Freestanding flexible microstructures fabricated from deposited thin films become mechanically unstable when internal stresses exceed critical values. A series of structures with varying geometries is used to determine the critical geometry at which buckling occurs. Observation with an optical microscope quickly reveals qualitative and quantitative information about the internal strain in the film. Strain values between +or-1.5% can be measured for a 2.0 mu m thick film using doubly-supported beams for compres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
98
0
1

Year Published

1999
1999
2007
2007

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 137 publications
(101 citation statements)
references
References 9 publications
2
98
0
1
Order By: Relevance
“…Recall from Equations (1) and (2) that the model indicates that everything about the pad is known if the equivalent length L~p and cross-sectional moment of inertia Z~Pare known. If Lo and Lb are defined as the equivalent support post cantilever lengths found using the (3'sand /5's,respectively, then and (4) (5) which are derived from Equations (1) and (2). If model 1 is correct, then these two equivalent lengths should be equal.…”
Section: Kuks Of Femmentioning
confidence: 99%
See 1 more Smart Citation
“…Recall from Equations (1) and (2) that the model indicates that everything about the pad is known if the equivalent length L~p and cross-sectional moment of inertia Z~Pare known. If Lo and Lb are defined as the equivalent support post cantilever lengths found using the (3'sand /5's,respectively, then and (4) (5) which are derived from Equations (1) and (2). If model 1 is correct, then these two equivalent lengths should be equal.…”
Section: Kuks Of Femmentioning
confidence: 99%
“…For example, cantilever beams have been used to measure curvature resulting from a strain gradient [1][2][3] as well as Young's modulus [3]. A number of researchers have also used fixed-fixed beams to measure residual stress [1][2][3][4][5][6][7]. Most of these researchers have concluded that boundary conditions at the beam ends significantly affect the accuracy of the measurements.…”
Section: Introductionmentioning
confidence: 99%
“…The total potential may be written in the following normalized form For any given ~ and Ẽ , the deflection of the beam at the critical buckling state can be derived by extracting the constant parameters from (11) and substituting them into the general solution (8). This calculation yields the mode of the deflection at the onset of buckling g x f,…”
Section: Post-emb Of a Clamped-clamped Beammentioning
confidence: 99%
“…In some of these structures the buckling phenomenon is utilized to measure residual stress. Notable among these passive test structures are clamped-clamped beams and Gukel rings [11]. Compressive residual stress can cause buckling in clamped-clamped beams.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation